(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this essay is to shed some light on how sex agrees with morphology in personal onomastics of the Iberian Peninsula and Gaul. Among suffixes used in gender derivation, -us appears as masculine and -a as feminine, but there are some instances which point out otherwise. Similarly, some names are specialized in one gender: in that respect, Reburrus (with 157 records) appears only in masculine, and Sunua (31 records) only in feminine. Semantics might be a reason for these uses.